A propósito da relação fala-escrita : um estudo comparativo da organização tópica de palestras e suas retextualizações - Marega, Larissa Minuesa Pontes (2009)
In this research we privileged the existing relations between the oral language and written language from a comparative approach between topic organization of formal elocution (lectures) and its written retextualizations. Our analysis corpus is constituted by three lectures of the event entitled "VI Encontro - O negro na Universidade: o direito a inclusão" (VI Meeting - The black man in University: the right of inclusion), that were transcribed and retextualized by UEM Teaching Project Midiatic Data Bank participants. Having this material, we stablished this work central objective: to observe if, as described by specialized literature, even similar in some points - international and situational assimetry, organizational macrostructure, thematic and compositional arrangement - these lectures and their retextualizations present representative topicality changes. Based on theoretical, terminological and analitic orientation of Conversation and Textual Linguistic Analysis, we selected the discursive topic as analitic proposed category of this work, such as postulated at Spoken Portuguese Project studies. To realize this research proposal, we identified discursive topics of spoken and written texts, basing on the centration principles, we built Topic Charts and explain tables that evidenced the vertical and lineal organization of the developed topics. We described, as well, the responsible elements for lectures topic segementation: centration, intertopic insert, topic statute insert, discursive markers, rests, transition topics, exemplifications, citations, metadiscursive, enunciative and interative marks, textual cohesion, summarizer paraphrasis; and the responsible for topic written retextualization segmentation: centration, paragraphation, textual cohesion. Data raising allowed us to realize the topicality comparation described in the lectures with found topicality in the retextualizations. In our comparative analysis, we found that there were, in fact, changes at the topical organization of these texts: reduction, substitution, elimination, adaptation, reordenation and internal topics movement. The investigated retextualization process of this job revealed several level alteration as well: semantics, lexical and syntatical.